2018
DOI: 10.5194/bg-15-1483-2018
|View full text |Cite
|
Sign up to set email alerts
|

Increasing coastal slump activity impacts the release of sediment and organic carbon into the Arctic Ocean

Abstract: Abstract. Retrogressive thaw slumps (RTSs) are among the most active thermokarst landforms in the Arctic and deliver a large amount of material to the Arctic Ocean. However, their contribution to the organic carbon (OC) budget is unknown. We provide the first estimate of the contribution of RTSs to the nearshore OC budget of the Yukon Coast, Canada, and describe the evolution of coastal RTSs between 1952 and 2011 in this area. We (1) describe the evolution of RTSs between 1952 and 2011; (2) calculate the volum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 63 publications
(94 reference statements)
0
33
0
Order By: Relevance
“…No disturbances in peat accumulation were indicated in low‐centered Ptarmigan Polygon (this study), nor in a low‐centered ice‐wedge polygon studied on Herschel Island, which showed undisturbed peat formation for the last 3000 years. The main Holocene and modern sources of disturbance on the Yukon Coastal Plain are mass wasting processes linked to increased coastal erosion and thermokarst as well as thermal erosion . The question of whether disturbance triggered later drainage of the polygon centers and finally led to relief inversion cannot be answered at this stage, but will be worth investigating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No disturbances in peat accumulation were indicated in low‐centered Ptarmigan Polygon (this study), nor in a low‐centered ice‐wedge polygon studied on Herschel Island, which showed undisturbed peat formation for the last 3000 years. The main Holocene and modern sources of disturbance on the Yukon Coastal Plain are mass wasting processes linked to increased coastal erosion and thermokarst as well as thermal erosion . The question of whether disturbance triggered later drainage of the polygon centers and finally led to relief inversion cannot be answered at this stage, but will be worth investigating.…”
Section: Discussionmentioning
confidence: 99%
“…The main Holocene and modern sources of disturbance on the Yukon Coastal Plain are mass wasting processes 86,87 linked to increased coastal erosion 88 and thermokarst 64 as well as thermal erosion. 89 The question of whether disturbance triggered later drainage of the polygon centers and finally led to relief inversion cannot be answered at this stage, but will be worth investigating.…”
Section: Climate Vs Geomorphic Disturbances As Drivers Of Change Imentioning
confidence: 99%
“…Thawing permafrost and deepening of the active layer lead to the mobilization of this carbon (Osterkamp, 2007;Woo et al, 2008), the release of carbon dioxide (CO 2 ) and methane (CH 4 ) to the atmosphere (Schaefer et al, 2014), and an increase in riverine dissolved organic carbon (DOC) fluxes (Frey and Smith, 2005;Le Fouest et al, 2018). Also associated with warming is the development of surface (physical) disturbances such as active layer detachments or retrogressive thaw slumps (Lacelle et al, 2010;Lamoureux and Lafrenière, 2009;Lewkowicz, 2007;Ramage et al, 2018) and thermal perturbation of the subsurface (Lafrenière and Lamoureux, 2013). As these processes influence freshwater systems, they ultimately have impacts on the biological production and the biogeochemistry of the Arctic Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Erosional processes in the permafrost coast result in release of large amounts of sediment and organic matter to the nearshore zone . For example, the mean annual rates of sediment release due to coastal erosion are estimated to range between 800 and 5400 m 3 /km/yr (m 3 per km coastline per year) in the Barents, Kara, Laptev, East Siberian and Russian Chukchi Seas (e.g., ).…”
Section: Discussionmentioning
confidence: 99%